The influence of genetic predisposition to oxidative stress on painful diabetic peripheral neuropathy: A mendelian randomization study: Genetic oxidative stress impact on diabetic neuropathy pain - Zou, Liyan; Zhu, Duosheng; Gong, Min; Yu, Jiangyi (Cellular and Molecular Biology, 2024)
Genetic predisposition to oxidative stress (OS) may influence the risk of Painful Diabetic Peripheral Neuropathy (PDPN). This study employed a Mendelian Randomization (MR) approach to investigate the causal relationship between genetic predisposition to OS and PDPN. Genetic instruments associated with OS biomarkers were selected as exposures. Summary-level data on PDPN was obtained from the largest available genome-wide association study (GWAS). MR analyses were conducted using the inverse-variance weighted (IVW) method, with sensitivity analyses employing the MR-Egger, weighted median, and MR-PRESSO approaches. Genetic predisposition to increased glutathione S-transferase (GST) activity was associated with a reduced risk of PDPN (OR=0.66, 95%CI: 0.49-0.89, P=0.006). Higher ascorbate levels conferred a protective effect against PDPN (OR=0.83, 95%CI: 0.71-0.97, P=0.018). No significant association was observed between genetic predisposition to OS biomarkers and PDPN severity. Genetic predisposition to increased GST activity and higher ascorbate levels protect against the development of PDPN, suggesting a causal relationship.